Analisis Morfometrik Kerbau Lumpur (Bubalus bubalis) Kabupaten Karo Sumatera Utara - falentino sembiring (Jurnal Peternakan Integratif, 2013)
ABSTRACT   Identification through morphometric swamp buffaloes in Karo District North Sumatra, is expected to bring out the best location for the development of swamp buffaloes through observations into three sub-districts based population of swamp buffalo, the less population, medium population and the most population, which are Kabanjahe sub-district, Mardingding sub-district and Munte sub-district. Samples obtained as much as 88 buffaloes. The method used in this research is a survey method using Principal Component analysis with use of the Statistical Package for the Social Sciences (SPSS) program. The results showed that the special identifier swamp buffalo in Karo was high hips, high shoulders and a wide chest for size.Wide chest, in chest and hip high for shape. Swamp buffalo who scored the greatest shape contained in the Kabanjahe sub-district and size swamp buffalo most of these are in Mardingding sub-district, so the good location for the development of swamp buffalo is in Mardingding sub-district. Keywords:  Swamp   buffalo,   morphology   of   swamp  buffalo, morphometrics of swamp buffalo, principal component analisys, karo district   ABSTRAK   Melalui identifikasi morfometrik kerbau lumpur di Kabupaten Karo Sumatera Utara, diharapkan akan memunculkan lokasi yang terbaik untuk pengembangan kerbau lumpur melalui pengamatan tiga kecamatan berdasarkan populasi kerbau lumpur yang terdiri dari daerah seedikit, sedang dan banyak, yaitu Kecamatan Kabanjahe, Kecamatan Mardingdind dan Kecamatan Munte. Sampel yang diperoleh sebanyak 88 ekor. Metode yang digunakan dalam penelitian ini adalah metode survei dengan menggunakan analisis Komponen Utama yang dengan penggunaan program Statistical Package for the Social Sciences (SPSS).  Hasil penelitian menunjukkan bahwa penciri khusus kerbau lumpur di Kabupaten Karo adalah tinggi pinggul, tinggi pundak dan lebar dada untuk ukuran serta lebar dada, dalam dada dan tinggi pinggul untuk bentuk. Kerbau lumpur yang memiliki skor bentuk paling besar terdapat di Kecamatan Kabanjahe dan ukuran kerbau lumpur yang paling besar terdapat di Kecamatan Mardingding, sehingga lokasi yang baik untuk pengembangan kerbau lumpur adalah di kedua kecamatan tersebut.   Kata Kunci :   Kerbau lumpur, morfologi kerbau lumpur, morfometrik kerbau lumpur, analisis komponen utama, kabupaten karo